A HISTORICAL STUDY OF THE LEGACY OF UTPALA DYNASTY IN KASHMIR, WITH SPECIAL REFERENCE TO AVANTIVERMAN (855-883 A.D.) - Shabir Ahmad Lone (Journal of International Islamic Law, Human Right and Public Policy, 2025)
Jammu and Kashmir, often referred to as "heaven on Earth," has long captivated rulers and poets alike. The famous Persian couplet by Amir Khusrau describes it as unparalleled in beauty, inspiring numerous rulers to vie for control over the region. The Rajatarangini, a metrical chronicle, narrates Kashmir's dynastic history from the Mahabharata era to Sangrama Deva's reign. Avantivarman, a significant ruler of the Utpalas dynasty established in 855 CE, heralded a golden age for Kashmir. Eschewing military conquests, he prioritized peace and prosperity, ushering in a period of unparalleled stability and contentment. His reign, approximately 25 years into his rule, marked Kashmir's zenith in terms of happiness and economic well-being. Avantivarman, though not from a distinguished lineage, exhibited exceptional leadership qualities. His administration not only alleviated the populace's suffering but also revitalized the region's cultural and political legacy, symbolizing a transformative era in Kashmir's history.